The development of functional requirements for the management of electronic court records at the Malaysian court of apppeal / Nurussobah Hussin - Hussin, Nurussobah (2014)
Technological change has always been a challenge to archivists, record practitioners, and IT personnel. The management of physical records fails to be regulated in the electronic environment as information systems fail to capture the necessary information needed and to function for long-term preservation. In the legal environment, the scope of legislation is referred to as its jurisdiction and, if not clear, can create difficulties for record managers and archivists to manage the court records. Regrettably, based on the preliminary investigation, there are no comprehensive policies or procedures for managing electronic court records in the Superior Court of Malaysia. Therefore, this study was undertaken with the aim to develop functional requirements for the management of electronic court records in the Malaysian Court of Appeal. This study only covers the Court of Appeal since the preliminary investigations revealed that the Court of Appeal is the most critical court in implementing the electronic system and it is most appropriate. The development of the functional requirements was based on three objectives: a) to identify and analyze various international and national best practices of functional requirements for electronic records management and functional standards for court; b) to investigate the current practices of the records management system in the Court of Appeal; and c) to evaluate the applicability of functional requirements developed on the practices of records management system in the Court of Appeal. This study was conducted using single-case design method involving qualitative approach i.e. content analysis, semi-structured interviews, and focus group discussions. In accomplishing the aim and objectives of the study, the research strategy was overall appropriate. In summary, the functional requirements developed are not only meant to assist in designing related system but also to assess the capability of software packages that is currently in place. The documented functional requirements could well be used for identifying missing functional components of the system, appraising and auditing the court records. The functional requirements could also be used as an input to re-examine and re-engineer existing business processes, thereby contributing to increased efficiency in court operations.